Pemisahan Uranium dari Thorium pada Monasit dengan Metode Ekstraksi Pelarut Alamine - Trinopiawan, Kurnia; Prassanti, Riesna; Sumarni, Sumarni; Pudjianto, Rudi (BRIN Publishing, 2011)
The research of monazite processing have obtained the process to recover 62% of rare earth elements (REE) from following steps, such as decomposition, partial dissolution, precipitation at pH 6,3, and precipitation at pH 9,8. There was an increased efficiency of the process in 2009, when ion exchange is used in process development, and the REE recovery became 85%. Besides REE, monazite processing also produce uranium and thorium, but they not separated individually yet. The research of the U from Th separation from pH 6,3 precipitate dissolution by H2SO4, is carried out using solvent extraction method, which the extractant consist of Alamine-336, kerosene, and isodecanol. This research is purposed to obtain the optimum condition of separation uranium from thorium with solvent extraction, where U separated from Th as best as it could . The research’s parameters are feed pH, O/A ratio, and extraction time. And the result showed that the optimum condition were 1,5 of pH, 5 of O/A ratio, and 5 minutes of extraction time, and the percentage of U extracted was 100%, but 32,44% of Th also extracted. From the result, it has a conclusion that 67,56% of Th could be separated from U.